(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
The application of nanotechnology in concrete adds new content to efforts to improve its performance. Due to the very small size of nano materials, the properties of concrete can be influenced by changing the microstructure. The study involved the use of Silica fume (3%,6%,9%) and nano-silica (1%,2%,3%) b.w.c. As the percentage of Silica fume and nano silica increases, an increase in strength is observed. Concrete is the material of present and future, It’s widespread use in structures, from buildings to factories, bridges and airports, makes it one of the most searched material. Due to rapid population explosion and the rise of technology to meet these needs, there is an urgent need to improve the strength and durability concrete. Among the various materials used in concrete production, cement plays an important role due to its size and adhesive properties. Therefore, for the production of improved concrete, the cement humidification mechanism should be studied properly and better alternatives should be proposed. In this study, the cement is replaced by silica fume and nano silica materials. In addition, it is planned to determine the number of predictions of cubes in the program. These theses explore the standard optimization ratio for silica and fume to get the best compressive strength. Further this has to check for Indian standard uses for developing the demand of quality users in India. All of the concrete mixtures were tested. These tests include performing Slump, compressive strength test. 24 cubes were molded for compressive strength, curing ages of 7,28 days for the concrete mixtures were applied in this work. The results proved the increase in compressive strength, durability, and various other properties of concrete by adding nano silica and silica fume in concrete.